2022
DOI: 10.1186/s12890-022-02049-0
|View full text |Cite|
|
Sign up to set email alerts
|

Adherence and quality of life assessment in patients with asthma treatment with budesonide/formoterol via the Elpenhaler device: the COMPLETE study

Abstract: Background Asthma is a chronic inflammatory disease of the airways that causes recurring episodes of wheezing, breathlessness, chest tightness and coughing. Inhaled drugs on a daily basis are the cornerstone of asthma treatment, therefore, patient adherence is very important. Methods We performed a multicenter, open, non-interventional, observational, prospective study of 716 adult patients diagnosed with asthma receiving FDC (Fixed-dose combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…This association was particularly identified with the asthma-specific questionnaire PROMIS-PAIS, likely due to its focused content, which is potentially more responsive to asthma symptoms ( Wiebe et al, 2003 ). Although the specific association of adherence with HRQoL has been less frequently examined, our results are consistent with findings of a systematic review in adolescents ( Usmani et al, 2018 ) and a multicenter, observational, prospective study in Greek adults with variable asthma severity ( Exarchos et al, 2022 ). Additionally, a longitudinal study in Dutch adolescents ( Tiggelman et al, 2015 ) indicated that higher HRQoL at baseline predicted increased medication adherence at follow-up, although good medication adherence did not predict an increase in HRQoL over time.…”
Section: Discussionsupporting
confidence: 89%
“…This association was particularly identified with the asthma-specific questionnaire PROMIS-PAIS, likely due to its focused content, which is potentially more responsive to asthma symptoms ( Wiebe et al, 2003 ). Although the specific association of adherence with HRQoL has been less frequently examined, our results are consistent with findings of a systematic review in adolescents ( Usmani et al, 2018 ) and a multicenter, observational, prospective study in Greek adults with variable asthma severity ( Exarchos et al, 2022 ). Additionally, a longitudinal study in Dutch adolescents ( Tiggelman et al, 2015 ) indicated that higher HRQoL at baseline predicted increased medication adherence at follow-up, although good medication adherence did not predict an increase in HRQoL over time.…”
Section: Discussionsupporting
confidence: 89%
“…This association was particularly identified with the asthma-specific questionnaire PROMIS-PAIS, likely due to its focused content, potentially more responsive to asthma symptoms [78]. While the specific association of adherence with HRQoL has been less frequently examined, our results are consistent with findings of a systematic review in adolescents [20] and a multicenter, observational, prospective study in Greek adults with variable asthma severity [79]. Additionally, a longitudinal study in Dutch adolescents [30] indicated that higher HRQoL at baseline predicted increased medication adherence at follow-up, although good medication adherence did not predict an increase in HRQoL over time.…”
Section: Adherence To Ics-based Maintenance Treatmentsupporting
confidence: 87%
“…Conversations between physicians and patients addressed ICS overuse and lack of knowledge and beliefs about ICS. Exarchos et al [54] examined the adherence levels of 716 adult patients diagnosed with asthma receiving budesonide/formoterol fixed-dose combination (FDC) via the Elpenhaler device. The study showed that about 80% of patients presented a moderate to high level of adherence during the study.…”
Section: Medication Adherence In Asthmamentioning
confidence: 99%